PENGARUH KOMPETENSI KERJA TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI KERJA SEBAGAI MEDIASI DI KANTOR PERTANAHAN KABUPATEN KAPUAS KALIMANTAN TENGAH - Qomari, Nurul; Claudia, Meiske (Universitas Lambung Mangkurat, 2023)
This research was conducted to determine and analyze (1) the effect of work competence on the performance of Non-Civil Servant Government Employees (PPNPN) at the Kapuas Regency Land Office; (2) the effect of work competence on the work motivation of non-civil servant government employees (PPNPN) at the Kapuas Regency Land Office; (3) the effect of work motivation on the performance of Non-Civil Servant Government Employees (PPNPN) at the Kapuas Regency Land Office; (4) the effect of work motivation as a mediation of the relationship of work competence on the performance of non-civil servant government employees (PPNPN) at the Kapuas Regency Land Office. Research respondents were 30 non-civil servant government employees (PPNPN) at the Kapuas Regency Land Office. The data was collected through a questionnaire in order to provide an assessment of work competence (X), test work motivation as a mediation (Z) and measure how much employee performance is to the organization (Y). The data analysis method used is Partial Least Square (PLS)3. The results of the study show that, Work Competence has no significant effect on the performance of PPNPN, Work Competencehas a significant effect on work motivation, work motivation has a significant effect on employee performance and work competence has a significant effect on employee performance through the role of mediating work motivation